Complications as poor prognostic factors in patients with hemorrhagic stroke: A hospital-based stroke registry - Rizaldy Taslim Pinzon; Vincent Ongko Wijaya (Romanian Journal of Neurology, 2020)
Introduction. Stroke patients commonly experience various medical complications during their rehabilitation stay. Understanding complications in hemorrhagic stroke patients can determine the patients prognosis. Aim. This study aimed to explore complications as prognostic factors among patients with hemorrhagic stroke. Methods. This was an observational analytic study with retrospective design. We analyzed the medical records of 480 patients admitted with hemorrhagic stroke between 2017 and 2018 at Bethesda Hospital, Indonesia. Disability, mortality, and length of stay (LoS) were assessed as clinical outcomes for this study. Multivariate logistic regression was used to analyze the data Results. The data were obtained from 480 patients with hemorrhagic stroke that majority of males (58.5%), with < 60 years old (52.3%), stroke onset > 3 hours (87.5%), and had stroke for the first time (82.9%). The most common complications was GI tract bleeding (19.8%), whereas the least was decubitus ulcer (1.5%). There were 25.8% patients died during hospitalization period. Among 356 survivors, there were no significant prognosis factors of disability in subjects. Logistic regression found stroke onset > 3 hours (OR: 0.34; 95%CI: 0.19-0.59; p < 0.001) and GI tract bleeding (OR: 30.8; 95%CI: 16.93-55.88; p < 0.001) to be an independent predictors of mortality in hemorrhagic stroke, whereas GI tract bleeding (OR: 0.54; 95%CI: 0.31-0.95; p = 0.03) and UTI (OR: 4.73; 95%CI: 1.11-20.1; p = 0.04) were also an independent predictors of prolonged length of stay in hemorrhagic stroke. Conclusion. This study identify complications as prognostic factors in hemorrhagic stoke patients. Stroke onset > 3 hours, GI tract bleeding, and UTI were independent predictors of poor prognosis in hemorrhagic stroke. There were no prognosis factor that affects disability in subjects.